PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP PRICE EARNING RATIO DENGAN TINGKAT SUKU BUNGA SEBAGAI VARIABEL MODERASI - Dwi Susanti; Maretha Ika Prajawati (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The purpose of this study is to determine the interest rate to moderate the effect of the Current Ratio and Debt to Equity Ratio on the Price Earning Ratio. The population of this study consisted of 49 companies and a sample of 8 companies in the property, real estate and building construction sectors listed on the Indonesia Stock Exchange from 2018 to 2021, selected through the purposive sampling method. The data were analyzed using linear regression analysis and moderation using the SPSS 25 program. The test results prove that the current ratio has no effect on the price-earning ratio, the debt-equity ratio has a significant positive effect on the price earning ratio, while the interest rate is unable to moderate the effect of the current Ratio to Price Earning Ratio, and interest rate are not able to moderate the effect of Debt to Equity Ratio to Price Earning Ratio. Tujuan dari penelitian ini ialah guna mengetahui tingkat suku bunga untuk memoderasi pengaruh current ratio dan debt to equity ratio terhadap price earning ratio. populasi penelitian ini terdiri dari 49 perusahaan dan sampel sebanyak 8 perusahaan pada sektor property, real estate dan konstruksi bangunan yang terdaftar di Bursa Efek Indonesia dari tahun 2018 sampai dengan tahun 2021, dipilih melalui metode purposive sampling. Data dianalisis menggunakan analisis regresi linier serta moderasi menggunakan program SPSS 25. Hasil pengujian membuktikan bahwa current ratio tidak berpengaruh terhadap price-earning ratio, debt-equity ratio ada pengaruh positif yang signifikan terhadap price earning ratio, sedangkan tingkat suku bunga tidak mampu memoderasi pengaruh Current Ratio terhadap Price Earning Ratio, dan tingkat suku bunga tidak mampu memoderasi pengaruh Debt to Equity Ratio terhadap Price Earning Ratio.